On the impact of health protocols in reducing the spread of COVID-19 virus: Analytical approaches through game, reaction network and SEIR models - De Leon, Sophia Alexandria T. (Animo Repository, 2022)
The COVID-19 is a global pandemic that has threatened the entire world. Through the advice of scientists and health oﬀicials, governments have made various interventions such as imposing rules regarding social distancing and wearing of masks and even administering vaccines to the public. All of these are meant to minimize the spread of the virus and yet there are individuals who would rather choose not to comply with these health protocols. This study aims to explore some approaches that will help analyze the impact of health protocols in the reduction of the spread of the COVID-19 virus using three mathematical models, namely, game, reaction network, and SEIR models. Seeing the situation as a game, the conditions that lead to the attainment of the Nash equilibrium were examined. Then, a reaction network from the game model was formulated. Consequently, various situations that tell when a noncompliance move becomes more beneficial than compliance to individuals in a population were considered. Lastly, an SEIR model was used to determine the possible trend of infection in a population where the eﬀicacy of interventions and percentage of compliance are considered with parameters referenced from Philippine COVID-19 data. With this study, the discussions on the above- mentioned models are expected to be helpful for those who are interested in studying the mathematical foundations of these. Readers will understand how situations like the pandemic may be analyzed using different methods that are anchored on mathematical theories.